Endogenous timing of moves in an asymmetric price-setting duopoly - Tasnádi, Attila (2018)
This paper adds to the growing literature on endogenous timing of de- cisions in duopolies. We show for a price-setting duopoly game with sufficiently asymmetric and strictly convex cost functions that the less efficient firm moves first while the more efficient moves second with a higher price than the less efficient firm.